The take-off of Israeli high-tech entrepreneurship during the 1990s a strategic management research perspective. - Fiegenbaum, Avi (Emerald, 2007)
Within less than a decade, during the 1990s, the state of Israel established its global high tech sector. The number of startups rose to almost 3,000. Total venture capital available reached approximately $ 3 billion. Israeli firms trading on NASDAQ climbed to 120 with aggregate market value of approximately $120 billion, twice the Israeli GNP. This book emphasizes the multilevel nature of this development from a strategic management perspective. The first level focuses at the country global processes emphasizing the entry of foreign multinational corporations and the privatization of state owned enterprises. The second level focuses on the government and its role in establishing the technological incubators and venture capital industries. The third level focuses on the sources of new start ups and the role of veterans of elite technological units of Israel Defense Forces and women entrepreneurs.-The fourth level focuses on the emerging organizations and the role of the board of directors and competitive intelligence capabilities and practices. Finally, the fifth level focuses at the industry level, emphasizing the role of the large number of new firms in creating new industrial sectors. The multilevel paradigm describes the sequential effects, starting at the first global level, and the interactive effects, across all five levels. The book provides insights that can aid academic researchers, company executives and public policy makers in understanding high tech takeoff. It is especially interesting and important given the turbulent environment mixed with the optimism of the peace process of Israel in the Middle East during the 1990s. It is an aid for academic researchers, public policy makers, and company executives for understanding high tech takeoff.-It conceptualizes the success of Israeli high-tech as a multilevel operation consisting of global, governmental, sources of new start ups, organizational, and industrial factors. It discusses each of these factors individually and the interaction between them.
Includes index.
Keywords: High technology industries -- Israel.; elektronické knihy; electronic books